Colonization of the vegetative stage of rice plants by the false smut fungus Villosiclava virens, as revealed by a combination of species‐specific detection methods. (11th May 2016) - Tanaka, E.; Kumagawa, T.; Ito, N.; Nakanishi, A.; Ohta, Y.; Suzuki, E.; Adachi, N.; Hamada, A.; Ashizawa, T.; Ohara, T.; Tsuda, M.
Abstract : Rice false smut disease caused by the ascomycete fungus Villosiclava virens (Clavicipitaceae) reduces rice yield worldwide. It invades rice panicles and forms dark‐green false smut balls composed of thick‐walled conidia. Although the infection process during the booting stage is well studied, its infection route before this is unclear. It was hypothesized that the thick‐walled conidia in soil penetrate rice roots, and the fungus latently colonizes roots and tiller buds at the vegetative stage. This hypothesis was tested using species‐specific detection methods. First, real‐time PCR with species‐specific primers and probe was used to estimate thick‐walled conidial number in the paddy field soil. Secondly, nested PCR with species‐specific primers showed that fungal DNA was detected in roots and shoot apices of rice plants in the vegetative stage. Thirdly, colourimetric in situ hybridization with a species‐specific oligonucleotide probe targeting 18S rRNA suggested that sparse mycelia or tightly condensed mycelia were present on the external surface of tiller buds enveloped by juvenile leaf sheaths at the vegetative stage. Thin hyphae were found around leaf axils at the surface of elongated stems at the heading stage, and the fungal hyphae grew in the rice root tissues. In addition, it was demonstrated that eGFP‐tagged transformants of the fungus invaded rice roots and colonized the surface of roots and leaf sheaths under artificial conditions.